INTUISI: Pendalaman Gagasan Hans-George Gadamer tentang Intuisi sebagai Supralogika - Rannu Sanderan (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2020)
This article explains about digging deeper of Hans-Georg Gadamer's ideas, in term of intuition as a supralogic. This study aim is to find out how the role of intuition develops a view of the goodness and the general truth. In this case, intuition allows someone to act wisely, also could live harmoniously in their community base. Research design: This research aims to describe Gadamer's view of intuition from the point of view of hermeneutic philosophy. The concept of humans is discussed more clearly by Gadamer in his own four ideas, that is: (1) bildung or culture, (2) sensus communis or conscience or heart, (3) consideration, and (4) taste. In this study, can be drawn that the idea of a communist census enables one to act almost intuitively. Implication and the result: Intuition or heart, heart or conscience has a social aspect, that is the sense of community, and by which we can gain knowledge and carry out interpretations. The Intuition approach as a supralogic is an openness to others, whatever its form, be it text, musical sounds or works of art, whose truth cannot be achieved by scientific methods. It is hoped that this study will bring benefit for cultural practitioners and education observers. Pendalaman gagasan Hans-Georg Gadamer tentang intuisi sebagai supralogika. Tujuan penelitian ini adalah hendak mengetahui bagaimanakah peran intuisi memperkembangkan suatu pandangan kebaikan yang benar dan umum? Dalam hal ini, intuisi memungkinkan seseorang bertindak bijak, hidup serasi di dalam komunitas. Penelitian ini hendak menguraikan pandangan Gadamer tentang intuisi dari sudut pandang filsafat hermeneutik. Konsep tentang manusia dibahas lebih luas oleh Gadamer dalam empat konsep, yakni bildung atau kebudayaan, sensus communis atau suara hati atau kalbu, pertimbangan dan taste atau selera. Dalam kajian ini, gagasansensus communis-lah yang memungkinkan seseorang bertindak hampir-hampir secara intuitif. Hasilnya, intuisi atau hati, kalbu atau suara hati mempunyai aspek sosial yaitu rasa komunitas, dan olehnya kita dapat mengetahui dan menginterpretasi. Pendekatan Intuisi sebagai supralogi adalah keterbukaan terhadap yang lain, apapun bentuknya, baik teks, bunyi musik atau karya seni, yang kebenarannya tak dapat dicapai dengan metode ilmiah. Kajian ini diharap memberi manfaat bagi pelaku budaya dan pemerhati pendidikan.